I-Nearly Prime Submodules - Abdul-AlKalik, Adwia J.; Al-Mothafar, Nuhad S. (Iraqi Journal of Science, 2019)
Let be a commutative ring with identity, and a fixed ideal of and be an unitary -module. In this paper we introduce and study the concept of -nearly prime submodules as genrealizations of nearly prime and we investigate some properties of this class of submodules. Also, some characterizations of -nearly prime submodules will be given.